Heat- and cold-induced gels of desalted duck egg white/gelatin mixed system: Study on rheological and gel properties. (December 2021) - Dai, Yalei; Zhao, Jingyun; Gao, Jin; Deng, Qianchun; Wan, Chuyun; Li, Bin; Zhou, Bin
Abstract: Our previous research had witnessed an efficient yet facile desalination method of salted duck egg white (SDEW) based on the reversible nature of gelatin (GEL) under mild conditions. This current study focused on engineering different gel systems based on desalted duck egg white/gelatin mixture (DDG), namely heat- and cold-induced gels, and the gel properties were further studied. Under the condition of small amplitude oscillatory shear (SAOS), the heat-induced DDG mixed gels has more linear viscoelastic regions and higher yield stress value than the cold-set gels. Additionally, the creep and recovery results demonstrated such heat-induced gels were harder but less elastic than that cold-induced gels. The strain hardening behavior of the gels was observed under high-amplitude oscillating shear. In the large amplitude oscillatory shear (LAOS) measurement, the Lissajous curves showed that in the elasticity analysis of these two different mixed gels, the heated hybrid gels were more elastic. As the content of GEL increased, GEL endowed higher water holding capacity of the hybrid gels. Compared with the cold-set gels, we found that the heat-induced mixed gels appeared a dense porous network microstructure, had greater impact on the water retention. In short, the different properties of constructed gels provided a new way for the utilization of desalted duck egg whites and basic data support for the construction of gel foods. Graphical abstract: Image 1 Highlights: Cold- and heat-induced gels were prepared by desalting duck egg white and gelatin. Heat-induced gels were stiffer but less elastic than cold-set gels. The heat-induced gels had more compact network microstructure.